Performance of coagulation, adsorption, ultrafiltration and hybrid treatment system on kaolin/humic acid removal - Low, Aik Qi (2018)
Conventional water treatment processes are not capable to meet the drinking water quality. With the aid of chemical use in the treatment process, it deteriorates the water quality by producing by-product that could affect the treated water. In line with this, this research aims to reduce the chemical use in the coagulation process. Therefore, hybrid or combination process is evaluated in this research project. Kaolin solution and humic acid were used as impurities normally found in the surface water and the process was evaluated in terms of turbidity (kaolin) and UV254 (humic acid) removal. In this study, three different individual processes (coagulation, adsorption, and ultrafiltration membrane) and three hybrid processes (coagulation-ultrafiltration, coagulation-adsorption, and coagulation-adsorption-ultrafiltration) are performed. For the adsorption study, natural plant-based material namely, mangosteen pericarp (MP) was used in this research as an adsorbent. The process used in the research experiment were jar test and membrane separation process for coagulation/adsorption and ultrafiltration respectively. Synthetic kaolin and humic kaolin water was used as test water in this research experiment. The parameter analyzed in this research include turbidity, UV254 and physical characterization on membrane and MP adsorbent. In the individual treatment process, the coagulation process could effectively remove the impurity in the water at pH 10 value up to 97% turbidity removal and 93% UV254 removal efficiency. Meanwhile, the solely mangosteen pericarp adsorbent used in the adsorption process did not effectively remove both turbidity and UV254. The ultrafiltration was able to remove the turbidity and UV254 up to 99% removal, however, the fouling would caused the flux permeate rate sharply reduced within first 6 minutes. The hybrid treatment process has shown higher removal efficiency and membrane relative flux. For the coagulation/ultrafiltration, its relative flux increased up to 12 and 30 times higher for the kaolin test water and HA-kaolin test water, respectively, as compared to the solely ultrafiltration process. The coagulation/adsorption at pH 8 shows better treated water quality. At pH 8 with 0.1 g of mangosteen pericarp adsorbent can harvest up to 99% of turbidity and UV254. Further subsequent ultrafiltration after coagulation/adsorption shows even higher relative flux which were 16 and 34 times higher for the kaolin test water and HA-kaolin test water respectively. The unique mangosteen pericarp adsorbent morphology and its surface adsorption volume has boosted hastening the sedimentation time consumed. In general, the hybrid system was shown a better performance than the individual process and it could reduce the chemical usage especially in coagulation, hence reduce the environmental impact on the waste issue in the treatment plant.